PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE, TIMELINESS, DAN DEBT TO EQUITY RATIO TERHADAP EARNING RESPONSE COEFFICIENT (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Rulfah M Daud; Nur Afni Syarifuddin (Program Magister Akuntansi Unsyiah, 2008)
The purpose of this research are: (1) the influence of corporate social responsibility disclosure an earning response coeficient (2) the influence of timelines on earning responsecoeficient, and (3) the influence of debt to equity ratio on earning response coeficient. This research use the hypotesis testing research with cencus method where the pupolation are investigated. Total of population is 19 (nineteen) companiesduring two year (2006-2007) observation (pooled data), 50 total pf population is 38 companies which analiysed by multiple linear regression model. Data used is annual report, financial report and stock information. The research results show that simultaneously, CSR disclosure, timeliness and debt to equity ratio influence to earning response coeficient. It explains that independent variabel coeficient (either CSR disclosure, timeliness, or debt equity ratio) is equol (0)(ß1 = 1,438, ß2 = 1,910, ß3 = -0,31). Particialy CSR disclosure influence to earning response coeficient positively. It denided the hypotesis which hope CSR disclosure influence to earning respone coeficient positively but, debt to equity ratio has negative influences. Keyword : Corporate social responsibility disclosure, timeliness, debt to equity, earning response coefficient.